Surface chemistry modulates osteoblasts sensitivity to low fluid shear stress. Issue 11 (30th January 2014) - Xing, Juan; Li, Yan; Lin, Manping; Wang, Jinfeng; Wu, Jinchuan; Ma, Yufei; Wang, Yuanliang; Yang, Li; Luo, Yanfeng
Abstract Low fluid shear stress (FSS) is the mechanical environment encountered by osteoblasts in implanted bones or native bones of bed rest patients. High sensitivity of osteoblasts to low FSS is beneficial to osteogenesis. We hypothesize that this sensitivity might be regulated by chemical microenvironment provided by scaffolds. To confirm this hypothesis, self‐assembled monolayers (SAMs) were used to provide various surface chemistries including OH, CH3, and NH2 while parallel‐plate fluid flow system produced low FSS (5 dynes/cm2). Alterations in S‐phase cell fraction, alkaline phosphatase activity, fibronectin (Fn), and collagen type I (COL I) secretion compared to those without FSS exposure were detected to characterize the sensitivity. Osteoblasts on OH and CH3 SAMs demonstrated obvious sensitivity while on NH2 SAMs negligible sensitivity was observed. Examination of the cell aspect ratio, orientation, and focal adhesions before and after FSS exposure indicates that the full spreading and robust focal adhesions on NH2 SAMs should be responsible for the negligible sensitivity through increasing the cell tolerance to low FSS. Despite the higher sensitivity, the Fn and COL I depositions on both OH and CH3 SAMs after FSS exposure were still less than on NH2 SAMs without FSS exposure. These results suggest that elaborate design of surface chemical compositions is essential for orchestration of surface chemistry with low FSS to realize both high sensitivity and high matrix secretion, facilitating the formation of functional bone tissues in implanted bone. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4151–4160, 2014.